Rapid and Sensitive Differentiating Ischemic and Hemorrhagic Strokes by Dried Blood Spot Based Direct Injection Mass Spectrometry Metabolomics Analysis - Hu, Zhansheng (J Clin Lab Anal, 2016)
Cerebral infarction (CI) and intracerebral hemorrhage are lethal cerebrovascular diseases, sometimes sharing similar clinical manifestations but with distinct therapeutic strategies. Delayed treatment usually resulted in poor prognosis. A timely diagnosis report is highly warranted especially in emergency. One hundred twenty‐nine CI patients, 73 intracerebral hemorrhage (ICH) patients, and 98 controls were enrolled in this study. A direct injection mass spectrometry metabolomics approach was adopted using dried blood spot samples. This targeted metabolomics analysis focused on absolute quantitation of 23 amino acids, 26 carnitine/carnitine esters, and 22 calculated ratios parameters. Compared to the normal control group, CI and ICH showed distinct metabolite changes, respectively. For stroke differentiation, Tyr, C5‐OH/C0, Cit, Asn, Pro, Val, Arg/Orn, Leu, and Val/Phe were elevated in the CI group. On the contrary, C5:1, Phe/Tyr, (C0 + C2 + C3 + C16 + C18:1)/Cit, and Met/Leu were of lower levels in the CI group. Using regression model based on some of the above‐mentioned parameters, 79.07% of stroke patients from a new set could be definitely confirmed. This study proved the targeted metabolomics analysis was a promising tool for rapid and timely stroke differentiation.